Positive effects of physical activity in autism spectrum disorder: how influences behavior, metabolic disorder and gut microbiota - Ranieri, Annaluisa; Mennitti, Cristina; Falcone, Noemi; La Monica, Ilaria; Di Iorio, Maria Rosaria; Tripodi, Lorella; Gentile, Alessandro; Vitale, Maria; Pero, Raffaella; Pastore, Lucio; D’Argenio, Valeria; Scudiero, Olga; et al. (Frontiers in Psychiatry, 2023)
Autism spectrum disorder is a neurodevelopmental disorder characterized by social interactions and communication skills impairments that include intellectual disabilities, communication delays and self-injurious behaviors; often are present systemic comorbidities such as gastrointestinal disorders, obesity and cardiovascular disease. Moreover, in recent years has emerged a link between alterations in the intestinal microbiota and neurobehavioral symptoms in children with autism spectrum disorder. Recently, physical activity and exercise interventions are known to be beneficial for improving communication and social interaction and the composition of microbiota. In our review we intend to highlight how different types of sports can help to improve communication and social behaviors in children with autism and also show positive effects on gut microbiota composition.